Regular linear extensions of dynamical systems on a torus - Kulik, V. L.; Kulik, L. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We consider certain structures of linear extensions of the dynamical systems on a torus having a single Green’s function.